2017
DOI: 10.1136/bmjinnov-2017-000203
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review of innovation design contests for health: spurring innovation and mass engagement

Abstract: We undertook a systematic review evaluating the effectiveness and cost of health-focused innovation design contests. We followed Cochrane guidance and systematically searched eight databases. Articles were included if they reported an open contest focused on improving health, required participants submit finished design solutions and contained a prize structure. We searched 3579 citations, identifying 29 health-focused innovation design contests which collectively received 15494 contest submissions. Contests s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 42 publications
0
65
0
Order By: Relevance
“…In comparison with previous systematic reviews [18,22], we included many more studies. This reflects the substantial growth in the field of crowdsourcing over the past several years.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison with previous systematic reviews [18,22], we included many more studies. This reflects the substantial growth in the field of crowdsourcing over the past several years.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
“…This is a major gap in the literature that requires attention. One example of an effective use of crowdsourcing in an RCT design includes a recently completed largescale, eight-city study of crowdsourcing to promote HIV testing [18], which demonstrated the value of crowdsourcing for enhancing public health campaigns. This systematic review data can be used to refine and standardize crowdsourcing approaches for specific healthcare contexts.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Crowdsourcing, allowing a group to solve a problem and then sharing the solution with the public, may help to improve public health programmes. Crowdsourcing can often take the form of participatory contests 2. Previous crowdsourcing contests have focused on producing individual components of communication programmes, such as videos,3 4 images5 6 or logos 7.…”
Section: Introductionmentioning
confidence: 99%